Introduction to food process engineering - Smith, P. G.; SpringerLink (Online service). (New York Springer, 2011)
Introduction to food process engineering treats the principles of processing in a scientifically rigorous yet concise manner, and can be used as a lead in to more specialized texts for higher study. It is equally relevant to those in the food industry who desire a greater understanding of the principles of the food processes with which they work. Written from a quantitative and mathematical perspective, this textbook is not simply a descriptive treatment of food processing. The aim is to give readers the confidence to use mathematical and quantitative analyses of food processes. To further this goal, each chapter includes a large number of worked examples and problems, with solutions provided in the back of the book. The mathematics necessary to read this book is limited to elementary differential and integral calculus and the simplest kind of differential equation. This second edition includes two additional chapters, Mass Transfer Operations and Minimal Processing Technology, as well as numerous new and revised figures.
Preface -- 1. An introduction to food process technology -- 2. Dimensions, quantities and units -- 3. Thermodynamics and equilibrium -- 4. Material and energy balances -- 5. The fundamentals of rate processes -- 6. The flow of food fluids -- 7. Heat processing of foods -- 8. Mass Transfer -- 9. Psychrometry -- 10. Thermal processing of foods -- 11. Low temperature preservation -- 12. Evaporation and drying -- 13. Solids processing and particle manufacture -- 14. Mixing and separation -- 15. Mass transfer operations -- 16. Minimal processing technology -- Appendix A: List of unit prefixes; Greek alphabet -- Appendix B: Fundamental and derived SI units; Conversion factors -- Appendix C: Derivation of a dimensionless correlation for film heat transfer coefficients -- Appendix D: Properties of saturated water and water vapour -- Appendix E: Derivation of logarithmic mean temperature difference -- Appendix F: Derivation of Fourier's first law of conduction -- Answers to problems -- Index.
Electronic reproduction.
Keywords: Food industry and trade; Electronic books